The diagnosis of latent tuberculosis infection (LTBI): currently available tests, future developments, and perspectives to eliminate tuberculosis (TB): The diagnosis of latent tuberculosis infection (LTBI) - Zellweger, Jean Pierre; Sotgiu, Giovanni; Corradi, Massimo; Durando, Paolo (La Medicina del Lavoro, 2020)
Introduction: Despite great efforts, tuberculosis (TB) is still a major public health threat worldwide. For decades, TB control programs have focused almost exclusively on infectious TB active cases. However, it is evident that this strategy alone cannot achieve TB elimination. To achieve this objective a comprehensive strategy directed toward integrated latent tuberculosis infection (LTBI) management is needed. Recently it has been recognized that LTBI is not a stable condition but rather a spectrum of infections (e.g., intermittent, transient or progressive) which may lead to incipient, then subclinical, and finally active TB disease. Aim: Provide an overview of current available LTBI diagnostic test including updates, future developments and perspectives. Results: There is currently no test for the direct identification of live MT infection in humans. The diagnosis of LTBI is indirect and relies on the detection of an immune response against MT antigens, assuming that the immune response has developed after a contact with the biological agent. Tuberculin skin test (TST) and interferon gamma release assays (IGRAs) are the main diagnostic tools for LTBI, however, both present strengths and limitations. The most ancient diagnostic test (TST) can be associated with several technical errors, has limited positive predictive value, is being influenced by BCG vaccination and several conditions can reduce the skin reactivity. Notwithstanding these limitations, prompt identification of TST conversion, should orientate indications for preventive therapy of LTBI. IGRAs have superior specificity, are not affected by M. bovis, BCG vaccination and other environmental mycobacteria. However, they present some logistical and organisational constraints and are more expensive. Currently, the WHO guidelines recommend that either a TST or an IGRA can be used to detect LTBI in high-income and upper middle-income countries with estimated TB incidences less than 100 per 100,000 population. Two skin tests (C-TB and Diaskintest), using only two specific M. tuberculosis antigens (ESAT-6 and CFP-10) instead of the tuberculin solution, have recently been developed but, to date, none of these tests is available on the European market. Conclusion: Early identification and treatment of individuals with LTBI is an important priority for TB control in specific groups at risk within the population: this is of crucial meaning in recently infected cases both at the community level and in some occupational settings. Currently there is no gold standard test for LTBI: an improved understanding of the available tests is needed to develop better tools for diagnosing LTBI and predicting progression to clinical active disease.